Studies Regarding New Genotypes for Table Grape Varieties Adapted to the Restrictive Conditions of North-Eastern Romania - Rotaru, Liliana; Colibaba, Cintia Lucia; Mustea, Mihai; Alexandru, Catalin Lulu; Cimpoi, Vladu Ion (Global Journal Of Botanical Science, 2019)
Table grapes’ genotypes are cultivated in ecosystem that exhibit a high degree of favourability from the point of view of the eco-climatic conditions, where large and qualitative productions, with a small percentage of rejects, are guaranteed, eliminating special technical interventions. Studies conducted on limitative biotope factors for vine culture show that the level of climatic and eco-pedological factors are favourable for the cultivation of different table grapes genotypes vine in Romania, both varieties for table grapes and wine, in well defined areas. The new created genotypes, namely Vitis vinifera L. Gelu and Vitis vinifera L. Paula, were taken into study. These new genotypes were created at the Research Station for Viticulture and Wine making Iasi, Romania. The study followed the technological and agro-biological values of the two varieties, compared with the control samples, genotype Vitis vinifera L. Aromat de Ia?i, for better discussing their production potential and quality characteristics, all influenced by the degree of adaptation to the climatic conditions that are in constant change.